2009
DOI: 10.3238/arztebl.2009.0262
|View full text |Cite
|
Sign up to set email alerts
|

Types of Study in Medical Research

Abstract: The study type that can best answer the particular research question at hand must be determined not only on a purely scientific basis, but also in view of the available financial resources, staffing, and practical feasibility (organization, medical prerequisites, number of patients, etc.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 25 publications
0
72
0
7
Order By: Relevance
“…Next, manual scoring (Figure 1a, Methods) revealed that only about half of the PubMed identified publications (n = 572, 54%) were primarily driven by Nigerian laboratories. From here, we categorised each remaining article as either basic research ('Basic', n = 255%, 45.5%) or 'clinical and epidemiological' research ('Clinical', n = 318%, 55.5%) based on the criteria for types of studies in medical research (Röhrig, du Prel, Wachtlin, & Blettner, 2009). This numerical dominance of clinical over basic research output is consistent with previous studies (Abd-Allah et al, 2016).…”
Section: Assess the Neuroscience Research Output From Nigeriamentioning
confidence: 99%
“…Next, manual scoring (Figure 1a, Methods) revealed that only about half of the PubMed identified publications (n = 572, 54%) were primarily driven by Nigerian laboratories. From here, we categorised each remaining article as either basic research ('Basic', n = 255%, 45.5%) or 'clinical and epidemiological' research ('Clinical', n = 318%, 55.5%) based on the criteria for types of studies in medical research (Röhrig, du Prel, Wachtlin, & Blettner, 2009). This numerical dominance of clinical over basic research output is consistent with previous studies (Abd-Allah et al, 2016).…”
Section: Assess the Neuroscience Research Output From Nigeriamentioning
confidence: 99%
“…Although the size of our cohort limits a comprehensive representation of national reporting trends, the chosen sources are all major news outlets in their respective countries and so likely provide a reasonable indication of broader trends. It was also assumed that all studies could be classified according to the model outlined by Röhrig et al [56].…”
Section: Limitationsmentioning
confidence: 99%
“…Randomisierte kontrollierte Studien gelten in der medizinischen Forschung als Goldstandard, sind aber kostenintensiv und schwierig durchzuführen [20]. …”
Section: Big Data Und Klinische Studienunclassified
“…ICD, SNOMED CT, HL7 sind bekannte Ansätze, medizinisch relevante Daten zu strukturieren und maschinell zu bearbeiten. Die reine Größe -68.000 ICD-10-Codes und mehr als 300.000 Konzepte in SNOMED CT [22] -gibt allerdings schon einen Eindruck von der Komplexität der Speicherung, des Managements und des Zugriffs auf derart kodierte Medizindaten [20,23].…”
Section: Technische Hürdenunclassified